PENGARUH MANAJEMEN LABA, LEVERAGE, KUALITAS AUDIT, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Sub Sektor Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2013-2018) - Ismail Feni; Anugerah Rita; Mela Fito Nanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the effect of earnings management, leverage, audit quality, liquidity and company size on the level of financial statement disclosure in sub-sector transportation companies listed on the Indonesia Stock Exchange (BEI). The data used in this study are secondary data, namely financial statements. The population in this study were all sub-sector transportation companies listed on the IDX for the 2013-2018 period. The number of samples in this study were 96 samples for 6 years using purposive sampling. The analysis technique in this study used multiple regression analysis and was performed using SPSS. The results of this study indicate that earnings management, leverage, audit quality, liquidity and company size have a significant effect on the level of financial statement disclosure in subtransportation companies listed on the Indonesia Stock Exchange (BEI) with significant values of 0.000, 0.015, 0.009, 0.000 and 0.000.Keywords: Earnings Management, Leverage, Audit Quality, Liquidity and Company Size, The Level of Financial Statement Disclosure